Effect of the Holiday Season on Weight Gain: A Narrative Review - Rolando G. Díaz-Zavala; María F. Castro-Cantú; Mauro E. Valencia; Gerardo Álvarez-Hernández; Michelle M. Haby; Julián Esparza-Romero (Journal of Obesity)
Several studies suggest that the holiday season, starting from the last week of November to the first or second week of January, could be critical to gaining weight. This study aims to review the literature to determine the effects of the holidays on body weight. In studies of adults, a significant weight gain was consistently observed during this period (0.4 to 0.9 kg, p<0.05). The only study in college students found an effect on body fat but not on weight (0.1 kg, p=0.71). The only study found in children did not show an effect on BMI percentile (−0.4%, p>0.05) during this period. Among individuals with obesity who attempt to lose weight, an increase in weight was observed (0.3 to 0.9 kg, significant in some but not in all studies), as well as increase in weight in motivated self-monitoring people (0.4 to 0.6%, p<0.001). Programs focused on self-monitoring during the holidays (phone calls and daily mailing) appeared to prevent weight gain, but information is limited. The holiday season seems to increase body weight in adults, even in participants seeking to lose weight and in motivated self-monitoring people, whereas in children, adolescents, and college students, very few studies were found to make accurate conclusions.